GUANINE CONTKNT OF SKIN OF SOME FISHES OF BOMBAY COAST - Manohar, S V (Indian Journal of Fisheries, 2011)
Among 13 fishes examined, Kati (Ilisha feligera) has the highest and Warn Muraenesox talatonoides) the lowest amount of guanine in their skin (1,219 and 115 mg guanine j>er 100 g skin). Muscle tissue contains no guanine.